Rojiroti microfinance and child nutrition: a cluster randomised trial. Issue 3 (10th October 2019) - Ojha, Shalini; Szatkowski, Lisa; Sinha, Ranjeet; Yaron, Gil; Fogarty, Andrew; Allen, Stephen John; Choudhary, Sunil; Smyth, Alan Robert
Abstract : Objective: To determine whether Rojiroti microfinance, for poor Indian women, improves child nutrition. Design: Cluster randomised trial. Setting: Tolas (village communities) in Bihar State. Participants: Women and children under 5 years. Interventions: With Rojiroti microfinance, women form self-help groups and save their money to provide loans to group members. After 6 months, they receive larger external loans. Tolas were randomised to receive Rojiroti immediately or after 18 months. Outcome measures: The primary analysis compared the mean weight for height Z score (WHZ) of children under 5 years in the intervention versus control tolas who attended for weight and height measurement 18 months after randomisation. Secondary outcomes were weight for age Z score (WAZ), height for age Z score, mid-upper arm circumference (MUAC), wasting, underweight and stunting. Results: We randomised 28 tolas to each arm and collected data from 2469 children (1560 mothers) at baseline and 2064 children (1326 mothers) at follow-up. WHZ was calculated for 1718 children at baseline and 1377 (674 intervention and 703 control) at follow-up. At 18 months, mean WHZ was significantly higher for intervention (−1.02) versus controls (−1.37; regression coefficient adjusted for clustering β= 0.38, 95% CI 0.16 to 0.61, p=0.001). Significantly fewer children were wasted in the intervention group (122, 18%) versus control (200, 29%; OR=0.46, 95% CI 0.28 to 0.74, p=0.002). Mean WAZ was better in the intervention group (−2.13 vs −2.37; β= 0.27, 95% CI 0.11 to 0.43, p=0.001) as was MUAC (13.6 cm vs 13.4 cm; β= 0.22, 95% CI 0.03 to 0.40, p=0.02). In an analysis adjusting for baseline nutritional measures (259 intervention children and 300 control), only WAZ and % underweight showed significant differences in favour of the intervention. Conclusion: In marginalised communities in rural India, child nutrition was better in those who received Rojiroti microfinance, compared with controls. Trial registration number: NCT01845545 .